Cannon Stored in Hugo Scheu Museum in Šilutė. Analysis of Artillery Cannons According to XRF Research Data - Vasiliauskas, Liudvikas (Archaeologia Lituana, 2021)
The article discusses the Swedish 3 pounds regimental cannon, produced in 1786.X-ray fluorescence (XRF) chemical element analysis data from cannon barrel alloys are also presented and discussed. As well as influence of their composition on the operation of cannons.
Keywords: artillery; cannon; regimental cannon; mortar; articulated cannon